Pendekatan Islam Hadhari ke arah memperkasakan identiti Melayu-Muslim di Malaysia - Jaffary Awang (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2009)
Islam Hadhari is a concept which is proposed purposely to develop the society. The issue closely related with the Malays is the aspect of strengthening the idenity of Malay Muslims. In order to face current challenges there is the need for strong values among all Malaysians, especially the Malays. This article will discuss Islam and Malays in relation with the past and the post Islamic resurgence. Futhermore, it will discuss the Malay identity issue which is hotly debated among the Malay Muslims intellectuals. This follows with the discussion on the relationship between Islam Hadhari and the development of the current Malay society. This article concludes that the concept of Islam Hadhari must be strengthened in order to improve the understanding of Islam amongs all Malaysians.